Design, Synthesis and Biological Evaluation of Novel (E)‐Hydroxystyryl Aralkyl Sulfones as Neuroprotective Agents. Issue 21 (2nd June 2020) - Chen, Ying; Hao, Yameng; Liu, Qian; Wu, Bolin; Liu, Yunqi; Zhang, Zhili; Tian, Chao; Ning, Xianling; Guo, Ying; Wang, Xiaowei; Liu, Junyi
Abstract: A novel class of ( E )‐hydroxystyryl aralkyl sulfones were designed and synthesized as neuroprotective agents. Their neuroprotective properties were assessed by several antioxidant models including 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) free radicals scavenging model, neuronal protective effects against neurotoxins such as hydrogen peroxide (H2 O2 ), 6‐hydroxydopamine (6‐OHDA) and 1‐methyl‐4‐phenylpyridinium iodide (MPP+). Besides, the anti‐inflammatory activity was evaluated by lipopolysaccharide (LPS)‐induced nitric oxide (NO) release model in BV2 microglial cells. The result demonstrated that cinnamyl substituted compound 5 h exhibited prominent antioxidant activity in H2 O2 and 6‐OHDA models and higher anti‐inflammatory potency (IC50 =7.3 μM) than lead compound 1 (IC50 =13.4 μM). Furthermore, compound 5 h displayed predicted CNS (+) blood‐brain barrier permeability ( P e =5.66×10 −6 cm s −1 ) in PAMPA model and low toxicity in PC12 and BV2 cells. These multifunctional properties highlight compound 5 h is a promising candidate for further development against neurodegenerative diseases. Abstract : In this paper, we focus on the role of catechol and phenyl in antioxidant and anti‐inflammatory activities. We find that catechol group is essential for the antioxidant activity, but not that important for anti‐inflammatory property. In addition, more than two phenolic hydroxyl groups reduced neuroprotective effects may be due to low permeability through cell membrane. Cinnamyl substituted phenylpropyl enhances the compound's anti‐inflammatory activity.